Elite Cues and the Rapid Decline in Trust in Science Agencies on COVID-19. (October 2021) - Hamilton, Lawrence C.; Safford, Thomas G.
The COVID-19 pandemic has been marked by political divisions in U.S. public trust of scientists. Such divisions are well known on other topics, but regarding COVID-19 they arose suddenly, with disastrous results. Distrust of scientists elsewhere has been variously explained in terms of belief systems, cognitive factors, peer influences, or elite cues. Three surveys conducted from March to July 2020 in the state of New Hampshire observed rapid change, providing a test of explanations in this case. Trust in science agencies such as the Centers for Disease Control and Prevention (CDC) fell dramatically among Republicans, while views among Democrats and Independents changed little; the Democrat–Republican gap grew from 10 to 64 points. This rapid change coincided with a reversal of views toward the CDC expressed by President Donald Trump and amplified by conservative media. People expressing lower trust in scientists also report less compliance with science-based behavioral recommendations and less support for scientifically informed policies.